Embedding components of entrepreneurship and creativity skills into construction technology education curriculum in Nigeria - Umar Muhammad Isa; Umar Lawal; Yahaya Ibn Salihu; Halliru Shuaibu; Abdullahi Musa Cledumas (Jurnal Pendidikan Teknologi dan Kejuruan, 2023)
Construction Technology Education (CTE) students in tertiary institutions of Nigeria have been criticised of their inability to demonstrate entrepreneurship and creativity skills after graduation. As such wood and building construction industries in Nigeria could not employ CTE graduates. Therefore, this study aims to determine entrepreneurship and creativity skills components appropriate for embedding into the curriculum of CTE program in Nigerian tertiary institutions. A qualitative research method involving intrinsic case study design was employed for the study. The population for the study comprised 16 CTE experts purposively selected from the tertiary institutions in the north western states of Nigeria. The study utilised a semi structured interview protocol as the instrument for qualitative data collection. 3 CTE experts from Nigerian tertiary institutions validated the protocol. Data from the interview responses were manually transcribed coded and interpreted. Findings from the responses of the participants revealed marketing skills, ICT skills, management skills as part of the entrepreneurship skills components appropriate to embedded into the curriculum of CTE program. The finding further revealed that critical thinking skills, innovative skills, and self-evaluation skills formed part of the creativity skills components appropriate for embedding into the curriculum of CTE program. The study concludes by recommending to the agencies responsible with running tertiary institutions in Nigeria to do the needful in restructuring the CTE curriculum at the undergraduate level to incorporate entrepreneurship and creativity skills components for employment sustainability of CTE students after graduation. Embedding Components of Entrepreneurship and Creativity Skills into Construction Technology Education Curriculum in Nigeria